Influence of Cohesive Zone Thickness on Gas Flow in Blast Furnace Analyzed by DEM‐CFD Model Considering Low Coke Operation. Issue 11 (4th September 2013) - Kon, Tatsuya; Natsui, Shungo; Matsuhashi, Shohei; Ueda, Shigeru; Inoue, Ryo; Ariyama, Tatsuro
<x xml:space="preserve">Abstract</x> Reduction of the reducing agent aiming at the mitigation of carbon dioxide emissions decreases the gas permeability in blast furnace. Favorable control of burden distribution and optimization of packed bed might mitigate decreasing permeability. Especially, decreasing thickness of cohesive zone would be effective. In present study, the influence of the cohesive zone thickness on gas flow and pressure distribution was investigated using the DEM‐CFD model to evaluate the effects of adoption of a thin‐layered cohesive layer structure on gas flow and permeability changes in the cohesive zone during low coke ratio operation. Reducing the thickness of the cohesive zone can effectively increase permeability in the cohesive zone even in the thin coke slit of the low coke rate operation, and improvement in the permeability of the cohesive zone can be realized more effectively in combination with appropriate coke mixed charging.